Atlas of endocrine pathology - Erickson, Lori A. (Atlas of Anatomic Pathology, 2014)
Atlas of Endocrine Pathology provides a comprehensive compendium of photomicrographs of common and uncommon entities in endocrine pathology. The volume includes histologic features of normal features, reactive conditions, hyperplasia, and tumors. The most helpful diagnostic features are illustrated to provide direction and clues to the diagnosis of endocrine tumors. Furthermore, photomicrographs highlight the most pertinent diagnostic features in problematic diagnoses in endocrine pathology.  Authored by a nationally and internationally recognized pathologist, Atlas of Endocrine Pathology is an important learning tool for those becoming familiar with the diverse entities encountered in endocrine pathology and a valuable reference for practicing pathologists faced with challenging diagnoses in endocrine pathology.